Experimental analysis of concrete with partial cement replacement using incinerated hospital waste ash - Iqbal, Muhammad Shoaib; Bux, Qadir; Ali, Afsar; Abdullahi, Saleh Mamman; Rahman, Abdur (Budownictwo i Architektura / Civil and Architectural Engineering, 2024)
The annual production of medical waste from healthcare facilities in Pakistan is around 250,000 tons. An effective waste management system is essential for disposing of hazardous medical waste, and incineration is considered the most effective and accessible technology. Disposal of medical waste ash in landfills without proper treatment could lead to groundwater contamination due to leachate. This research paper aims to evaluate the feasibility of using hospital waste ash obtained from the National Cleaner Production Center (NCPC) in Rawalpindi as a partial replacement for cement. The primary variable in this study was the amount of hospital waste ash (0%, 3%, 7%, and 10% by weight of cement), while the amount of cementitious material, water-to-cement ratio, and fine and coarse aggregate content were kept constant. A total of 36 cubes were cast, with nine cubes for each replacement level for curing periods of 7, 14, and 28 days. The slump value and density of fresh concrete decreased with the increase in the proportion of hospital waste ash in the mix. The compressive strength of mixes with 3% hospital waste ash was higher than that of the control mix. The best results (20.13 MPa) were obtained from the 3% mix after 28 days of curing, while the result obtained with the 7% mix was nearly equal to that of the control mix.